Development of activated hexagonal boron nitride for tribo-composite coatings using electroless nickel plating technique - Bello, Kamilu Adeyemi; Maleque, Md. Abdul; Ahmad, Zuraida; Mirdha, S. (2015)
The hexagonal boron nitride (hBN) is a potential solid lubricating material; however, it has few limitations such as less surface activation, poor wettability, inhomogeneous mixture with substrate materials etc. This can be overcome via co-deposition of highly activated materials. Therefore, the aim of this study is to co-deposit Ni-P alloy on hexagonal boron nitride (hBN) powder via electroless plating technique. The characterization of co-deposited hBN was performed by means of scanning electron microscopy (SEM). The morphologies of Ni-P co-deposited hBN suggested a good metallurgical bonding and uniform distribution of the powders with the existence of Ni3P phase. Elemental mapping also confirmed the deposition of Ni-P onto hBN substrate. Hence, it can be said that the co-deposition provides a highly active surface of hBN powder.